Managing International Migration for Development in East Asia - Adams, Richard H., Jr.; Ahsan, Ahmad (World Bank Group, Washington, DC, 2015)
The objective of this book is to analyze the economic and social impact of international migration on labor sending and labor receiving countries in the East Asia region. More specifically, the book seeks: (a) to examine the impact of international migration on key development indicators, including poverty, investment, labor force participation, labor productivity and wages; (b) to evaluate current government structures and institutions for managing migration, with a view to identifying future policies for maximizing the benefits of international labor migration. The book includes new work on these key policy issues from six East Asian countries: three labor sending countries (Indonesia, Philippines and Vietnam) and three labor receiving countries (Singapore, Malaysia and Thailand).